Therapeutic competence of dried garlic powder (Allium sativum) on biochemical parameters in lead (Pb) exposed broiler chickens - Hossain, Md. Anwar; Akanda, Md. Rashedunnabi; Mostofa, Mahbub; Awal, Md. Abdul (Journal of Advanced Veterinary and Animal Research, 2014)
The study was conducted to assess the therapeutic competence of garlic (Allium sativum) in lead (Pb) exposed chickens. The experimental birds (n=350) were grouped into T0 (as control), T1, T2, T3 and T4. The birds of group T1 was provided with lead acetate at 100 mg/kg body weight. Group T2 had lead acetate at 100 mg/kg b.wt. + 1% garlic supplement, whereas group T3 was fed with lead acetate at 100 mg/kg b.wt. + 2% garlic supplement, and group T4 had lead acetate at 100 mg/kg b.wt. + 4% garlic supplement. The mean values (mg/dL) of uric acid, blood urea nitrogen, creatinine, cholesterol, triglycerides, low density lipoprotein, high density lipoprotein, and blood glucose in the birds of group T1 were significantly increased (p<0.01) on day 42 of post-treatment. Elevation of these parameters was suggestive for the pathological involvement of different organs like liver, kidney, muscles. Statistical analysis of variance indicated that lead acetate at 100 mg/kg b.wt. + 2% garlic supplement (T3) resulted significant (p<0.01) ameliorative effect on the biochemical parameters as compared to the group T2 and T4. In conclusion, potency of garlic in reversion of the values of the biochemical properties in Pb exposed chickens was close to the normal levels of the values. http://dx.doi.org/10.5455/javar.2014.a34